Molecular phylogenetic analysis of commercially important Asian monsoon scallop, Amusium pleuronectes (Linnaeus 1758) from Indonesia - Eko Hardianto; Tony Budi Satriyo (Universitas Diponegoro, 2023)
The Asian monsoon scallop, Amusium pleuronectes, is a key member of shellfish communities that are the most commercially harvested in Asia. Materials were obtained from four sites in Indonesia: Semarang, Bali Island, Maros and Buru Island. Nucleotide sequence analysis was performed on PCR-amplified mitochondrial DNA 16S rRNA. In total, 556-558 base pair nucleotide sequences were obtained from 8 individuals. Molecular analyses revealed that the samples belong to the A. pleuronectes species. Phylogenetic analyses were carried out by comparing the gene sequences of A. pleuronectes haplotypes in Indonesia with gene sequences of the same base pair length and with the of A. japonicum which was used as an outgroup. The phylogenetic trees were consistent and indicated in the two sub-clades. The presence of A. pleuronectes and the phylogenetic status of the A. pleuronectes Indonesian haplotype were reported. Clarifying the phylogenetic status of ecologically important species provides basic information for biosecurity studies for possible future conservation and control programs.